One size fits all – utveckling av lärmiljöer för nyanlända elever i behov av specialpedagogiska stödinsatser - Johansson, Anna (Utbildning & Lärande, 2022)
This study aims to increase the understanding of how learning environments have been developed for newly arrived immigrant pupils in need of special educational support measures according to special educators. In this way, knowledge can be deepened about obstacles and opportunities in the school system regarding the development of learning environments, which can have an impact on these pupils’ learning. Free text responses from an e-questionnaire were analyzed through conventional content analysis. The analysis revealed varied descriptions of what characterizes the development of learning environments at schools. For example, many respondents described what characterizes as general adaptations as a kind of one size fits all solutions. Special educators also described support for language learning and language understanding in small groups, training for school staff and enhanced collaborations. The characterization of special educators´ descriptions is deepened and discussed with regard to obstacles and opportunities in the school system. To deepen the understanding, the results from this study are analyzed together with previous research and Skrtic’s (1991; 2005) concept of the school system, reflecting school bureaucracies and adhocracy. The obstacles in the development of learning environments are found in special solutions, lack of efforts and unclear areas of responsibility, while successes are found in training for school staff and enhanced collaborations in joint professional work.